Design and objectives of the South American youth/child cardiovascular and environmental (SAYCARE) Study (2018)
ABSTRACT: The purpose of this paper is to introduce the overarching study design of the South American Youth/Child Cardiovascular and Environmental (SAYCARE) study, which is an observational multicenter feasibility study held in seven South American cities: Buenos Aires (Argentina), Lima (Peru), Medellin (Colombia), Montevideo (Uruguay), Santiago (Chile), and Sao Paulo and Teresina (Brazil). Children and ~ adolescents (3-17 years of age) were studied. Methods: The data management systems, quality assurance monitoring activities, standardized operating procedure manuals, and training and study management are addressed in this paper. Various quality controls to ensure the collection of valid and reliable data are also discussed. Results and Conclusions: Data were obtained from 237 preschoolers and schoolchildren and 258 adolescents during the validation phase measurements. The results of the SAYCARE study are expected to provide higher accuracy in the assessment of cardiovascular disease risk factors, including eating behaviors, body composition, physical activity, sedentary behaviors, lipid profiles and cardiovascular health biomarkers, oral health, social conditions, environmental factors and home environment, and their determinants in children and adolescents from ages 3 to 17 in seven South American cities.